2014
DOI: 10.5901/mjss.2014.v5n20p2223
|View full text |Cite
|
Sign up to set email alerts
|

How Relevant is Talent Management in South African Local Government Institutions?

Abstract: Talent management is a concept increasingly on the minds of managers and practitioners, but still remain neither a strategic or operational priority in many organisations. The main objective of this research was to investigate the application of talent management practices in South African local government institutions (N=578). The results showed that talent management practices are poorly applied in the local government institutions. Significant gaps exist between the current applications versus the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…In addition the results also showed that large gaps exist between the current applications versus the perceived importance of between Talent Review Process, Retention Practices, Talent Development, and Management Commitment. In line with previous studies this research also confirms that talent management practices remain problematic in government institutions such as higher education (Barkhuizen, 2013;Magolego et al, 2013;Mtila et al, 2013). The results showed a significant positive relationship between some Talent Management and Work engagement dimensions.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In addition the results also showed that large gaps exist between the current applications versus the perceived importance of between Talent Review Process, Retention Practices, Talent Development, and Management Commitment. In line with previous studies this research also confirms that talent management practices remain problematic in government institutions such as higher education (Barkhuizen, 2013;Magolego et al, 2013;Mtila et al, 2013). The results showed a significant positive relationship between some Talent Management and Work engagement dimensions.…”
Section: Discussionsupporting
confidence: 78%
“…The effective talent management of employees has shown to increase their well-being , job satisfaction (Magolego, Barkhuizen & Lesenyeho, 2013), psychological contract (Mtila, Barkhuizen & Mokgele, 2013), organisational energy (Mpofu & Barkhuizen, 2013) and decreased turnover intentions (Barkhuizen & Veldman, 2012;Du Plessis, Stanz & Barkhuizen, 2013). Though several studies among South African government institutions pointed out that talent management practices are generally poorly applied or largely ignored (see Barkhuizen, 2013;Du Plessis et al, 2010;Magolego et al, 2013;Mtila et al, 2013;Mpofu & Barkhuizen, 2013).…”
Section: Talent Management and Work Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings disclosed that TM practices were not given due attention as seen in previous studies. The study done using exploratory factor analysis provided 66.88% with 95% confidence of variance interval greater than p value (P < 0.05) (Barkhuizen 2014).…”
Section: Findings Of Studies Done In Higher Education Institutionsmentioning
confidence: 95%
“…selection, succession, and performance management. (Wellins et al, 2004)" (p. 199) Chahal & Kumari (2013) "Applied within the public sector, we can refer to talent management as a concept that includes the attraction, training, development and retention of key employees while also taking into account the strategic goals of the client (Lockwood, 2005)" (p. 2223) Barkhuizen (2014) "According to Stockley (2005) talent management is a conscious, purposeful approach undertaken to attract, develop and retain people with the aptitude and abilities to meet current and future organisational needs." (p. 12) Barkhuizen et al (2014) …”
Section: Tm Definition Referencesmentioning
confidence: 99%